Bombing Hitler the story of the man who almost assassinated the Führer - Haasis, Hellmut G. 1942- (Skyhorse Publishing, 2015)
Georg Elser was just a working-class citizen living in Munich, Germany. He was employed as a carpenter and had spent some time working in a watch factory. That all changed when he took it upon himself, without telling his family or friends, to single-handedly attempt to assassinate the most powerful man in all of Germany: the Führer, Adolf Hitler. Elser's plan centered on the Munich beer hall, where he knew Hitler would be making a speech. Working slowly and in secret, he started to assemble the bomb that he would use to try to kill Hitler. When finished, the bomb was hidden in a hollowed-out space near the speaker's podium. The bomb went off successfully, killing eight people . . . but Hitler was not one of them.